Systems Biology
The rapidly developing methods of systems biology can help investigators to make inference and predictions from their data that intuition alone would not discern; however, the difficulty lies in the broad knowledge of mathematics and engineering that seems to be required to even evaluate the applicability of the methods to the problem at hand. In \\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\Systems Biology\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\, scientists who possess that mathematical knowledge and have applied it effectively to various biological problems contribute methods which reflect their experience, crystallized in a form very similar to typical biological laboratory protocols. In order to best aid researchers, the chapters supply the theory behind the method, its step-by-step implementation, and the pitfalls explained thoroughly and from the practical angle. As a volume of the highly successful Methods in Molecular BiologyÃƒÆ'Ã†â€™Ãƒâ€šÃ,Â¢ÃƒÆ'Ã,Â¢ÃƒÂ¢Ã¢â,¬Å¡Ã,Â¬Ãƒâ€¦Ã,Â¾ÃƒÆ'Ã¢â,¬Å¡Ãƒâ€šÃ,Â¢ series, this work provides the kind of detailed description and implementation advice that is crucial for getting optimal results. Cutting-edge and easy to use, \\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\Systems Biology\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\ shatters the perceived insurmountable barrier between the laboratory and systems-biological research techniques.